Use of Phosphodiesterase Inhibitors in the Postoperative Period of Skin Flaps: A Systematic Review - Daronch, Oona Tomiê [UNESP]; Marcante, Renata Fernanda Ramos [UNESP]; Neto, Aristides Augusto Palhares [UNESP]; Viterbo, Fausto [UNESP] (Wolters Kluwer, 2023)
Background: Ischemia-reperfusion injury can occur in several clinical conditions, and it has been widely studied in the context of skin flaps. Vascular distress results in an imbalance between the supply and demand of oxygen to living tissues, and the result of this process is tissue necrosis. Several drugs have been studied to reduce vascular distress of skin flaps and tissue loss. Methods: The present study performed a systematic review of literature in the main databases (PubMed, Web of Science, LILACS, SciELO, and Cochrane), including articles published in the last 10 years. Results: It was observed that phosphodiesterase inhibitors, mainly types III and V, have shown promising results in terms of vascularization of the postoperative skin flap, especially when started on the first postoperative day and maintained for 7 days. Conclusion: New studies with different posology, duration of use, and new drugs are needed to better elucidate the use of this substance to optimize the circulation of skin flaps.